2019
DOI: 10.3390/en12163148
|View full text |Cite
|
Sign up to set email alerts
|

High Throughput Screening and Characterization Methods of Jordanian Oil Shale as a Case Study

Abstract: Oil shale is an important possible solution to the problem of energy in Jordan. To explore the technical and the economic feasibility of oil shale deposits, numerous samples are analyzed using the standard Fischer Assay (FA) method. However, it would be useful to develop faster, cheaper, and reliable methods for determining the oil content of oil shale. Therefore, the aim of this work was to propose and investigate rapid analytical techniques for the screening of oil shale deposits and to correlate them with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…In addition, limited decomposition of the mineral material can occur, resulting in carbon dioxide production and the release of combined water. This was supported by the generated FTIR spectra ( Figure S1) and our previous work [15], which confirmed the production of CO 2 , as well as aliphatic and aromatic hydrocarbons.…”
Section: Thermogravimetric Analysissupporting
confidence: 85%
See 3 more Smart Citations
“…In addition, limited decomposition of the mineral material can occur, resulting in carbon dioxide production and the release of combined water. This was supported by the generated FTIR spectra ( Figure S1) and our previous work [15], which confirmed the production of CO 2 , as well as aliphatic and aromatic hydrocarbons.…”
Section: Thermogravimetric Analysissupporting
confidence: 85%
“…However, new technologies might overcome this limitation and could utilize higher heating rates. It was reported that increasing the heating rate lead to a non-significant increase in the yield of pyrolysis products but changed the quality of the products (higher specific gravity and heavier oil In the drying zone, there was a relatively low weight loss of less than 1.4 wt.%, which can be related to the devolatilization of surface and adsorbed water, entrapped gases, and light organic materials, as found by the generated FTIR spectra ( Figure S1, in Supplementary Materials) [15]. This low water content resulted in less heating requirements and less drying time for evaporation, thereby increasing the thermal efficiency of the retorter.…”
Section: Thermogravimetric Analysismentioning
confidence: 94%
See 2 more Smart Citations
“…Moving right on the spectrum toward lower wavenumbers, dactyloscopy region starts [20]. Small differences, e.g., different intensity ratios, or slightly different shapes of selected bands occur; however, region 800-650 requires more detailed analysis.…”
Section: Fat Characterization By Ft-irmentioning
confidence: 99%